Safety, intimacy and defiance in the context of border control and counter-smuggling: Algeria’s ghettos, maquis and ngandas - Arrouche, Kheira (Trends in organized crime, 2023)
There has been scant examination into how West and Central African migrants experience and respond to migration enforcement and counter-smuggling policies in the context of Algeria. In recent years, Algeria’s opaque migratory policies against both irregular migrants and all mechanisms facilitating their mobility –including incarceration and removal to remote parts of the country—have intensified. Drawing on ethnographic fieldwork, I examine migrants’ responses and encounters with the migrant community structures in Algeria. While navigating the state’s punitive policies, migrants also negotiate their daily lives and immobility experiences within particular social places where they become implicated in different forms of intimate economies, care and kinship, and reciprocity. In this paper, I examine two particular ambivalent social spaces: the ghetto, and the maquis or nganda, introduced by the migrant community in the context of migration enforcement and counter-smuggling controls. I provide an understanding of the role of solidarity and support provided by these spaces, which challenges and goes beyond their conventional perception as inherently exploitative. In addition, I look closely at labour intimacies framed as ‘pairing’ or ‘contra de décharge,’ which involve the affective entanglements present in male and female migrants’ mobility experiences. As the ghetto and the maquis support the migrants in mitigating the impact of the state’s policies and uncertainty during their im-mobility, it is also important to take into consideration their role in reproducing vulnerabilities due to the unequal power hierarchies and gendered dynamics that characterise their structural organisation.